Sportivno-ozdorovitel'naya programma "Przidentskie sostyazaniya" - Vavilov, Yu. N.; Vavilov, A. Yu. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
On the state-initiated program "Presidents Competitions" for the development of sports and health in Russian children (idea, history, structure).